2008
DOI: 10.1063/1.2998394
|View full text |Cite
|
Sign up to set email alerts
|

Gated armchair nanotube and metallic field effect

Abstract: We propose a useful metallic field effect element based on the electric field control of armchair single-wall carbon nanotube. The electron conduction channels are enhanced by imposing a transverse gate voltage. Multiple Dirac points have been revealed theoretically by our density functional and tight binding calculations. Our electron transport results show that the performance of such unique transistors depends mainly on the diameter of nanotube exploited. The critical field strength required decreases rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…For example, Zhang et al have observed experimentally that the longitudinal electronic transport of ZnO nanowires can be tuned by the transverse electric field. 5 On the other hand, it has been extensively proved theoretically that the electric field can efficiently modulate the electronic properties in numerous nanostructures, such as carbon NTs, [6][7][8][9][10][11] BN NTs, [12][13][14] SiC NTs, 15 GaN NWs and NTs, 16 Si NWs, 17 AlN nanoribbons, 18 and ZnO nanoribbons. 19 For instance, Yilmaz et al 16 have observed the transverse electric field can induce a homojunction across the diameter for the GaN NTs and NWs.…”
mentioning
confidence: 99%
“…For example, Zhang et al have observed experimentally that the longitudinal electronic transport of ZnO nanowires can be tuned by the transverse electric field. 5 On the other hand, it has been extensively proved theoretically that the electric field can efficiently modulate the electronic properties in numerous nanostructures, such as carbon NTs, [6][7][8][9][10][11] BN NTs, [12][13][14] SiC NTs, 15 GaN NWs and NTs, 16 Si NWs, 17 AlN nanoribbons, 18 and ZnO nanoribbons. 19 For instance, Yilmaz et al 16 have observed the transverse electric field can induce a homojunction across the diameter for the GaN NTs and NWs.…”
mentioning
confidence: 99%
“…10 However temperature introduces atomic displacements and significant backscattering for electronic states far away from the Fermi level E f while having only minimal effects on the linear bands crossing at E f . This effect roots in the fact that only two bands of different symmetries contribute to transport near Fermi level, 17 and the special topological properties of the dispersion near the Dirac point protects the system from backscattering between one band and the other at the same K point. Although K → KЈ backscattering is allowed, the long-range atomic displacement due to phonons is very insufficient in causing such large momentum transitions.…”
mentioning
confidence: 99%
“…In other words, the intrinsic electric field provided by electronegativity difference between hydrogen and fluorine at opposite sides of bismuth in Bi 2 HF nanosheet induces the band gap opening. The physical mechanism is similar to the situation of bilayer graphene 40 , 41 and other low dimensional materials 42 , 43 under the external electric field.
Figure 2 The electronic structure of Bi 2 HF nanosheet.
…”
Section: Resultsmentioning
confidence: 56%